MANAGERIAL STRATEGY IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION IN THE CONTEMPORARY ERA - Nur Hidayah; Yuniarti Yuniarti; Zamroni Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Islamic education in Indonesia faces multidimensional challenges in the contemporary era, not only in the form of intense competition between educational institutions but also increasingly complex quality demands and vulnerability to various crises. This article aims to comprehensively analyze the role of strategic management as a systematic approach to improving the quality of Islamic education. Through an in-depth literature review of various recent sources, this article outlines the nature of strategic management and the quality of Islamic education, identifies determinants that influence quality, explores the concept of crisis management in the context of Islamic education, and formulates a framework for effective strategic management implementation. The analysis shows that the quality of Islamic education is a multidimensional construct influenced by input factors (leadership, teachers, students, curriculum, infrastructure) and integrated managerial processes. The application of strategic management, which includes the stages of strategy formulation, implementation, and evaluation, has proven effective in guiding Islamic educational institutions to achieve their goals in a more structured, measurable, and adaptive manner to environmental changes. Furthermore, crisis preparedness through sound crisis management is an integral part of institutional resilience amidst uncertainty. It was concluded that the integration of visionary strategic planning, consistent implementation, continuous evaluation, and crisis preparedness is a strategic key for Islamic educational institutions to not only survive but also excel in holistically and sustainably improving the quality of their education amidst the dynamics of the times.